2011
DOI: 10.2478/s13531-011-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional simulation of air permeability of single layer woven structures

Abstract: The paper deals with a CFD based study of the transverse permeability of a textile woven structure. The reported numerical investigation is preconditioned by both previous experimental and CFD study on jet systems. It is also based on detailed experimental investigation of the porous structure of single layer woven fabrics, made of staple fiber yarns. The flow in through-thickness direction of the woven structures is presented as jet systems, issuing from set of orifices. Two different types of jet system (3×3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…It was found in our previous work 18 that there is no difference either in the numerical results, or in the required central processing unit (CPU) time in the simulation of the air flow, between jet systems with circular and square openings. Therefore, the choice of the shape of the pores would depend on the personal preference of the researcher and on the type of the grid used, which has to assure “high quality” of the control volumes, convergence promptness, etc.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found in our previous work 18 that there is no difference either in the numerical results, or in the required central processing unit (CPU) time in the simulation of the air flow, between jet systems with circular and square openings. Therefore, the choice of the shape of the pores would depend on the personal preference of the researcher and on the type of the grid used, which has to assure “high quality” of the control volumes, convergence promptness, etc.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…18 It was found that the fine grid gives best results and it was selected for the present investigation as well.…”
Section: Grid Typementioning
confidence: 99%
See 3 more Smart Citations